Education and Research: A Symbiosis to Better Understand a Novel Coral Disease - Soper, Deanna M. (Frontiers in Marine Science, 2021)
Ongoing ecological events, such as new and emerging diseases, provide an important platform for education and research. Field courses and undergraduate research projects can be critical to assisting students with learning scientific skills and career discernment as these experiences provide more one-on-one instruction and an immersive learning environment. A novel coral disease called “Stony Coral Tissue Loss Disease” (SCTLD) provided one such opportunity. SCTLD is characterized by rapid progression with entire coral heads dying within 2-3 weeks after initial observation of the onset of symptoms. At a wider geographic scale, the disease has migrated with extreme velocity and has now been documented across the Caribbean from as far North as the Southeast Florida Reef Tract, as far South as St. Lucia, and as far West as Honduras and Belize. Here, I summarize what is currently known about SCTLD and document an educational field course that involved eight undergraduate students with visits to multiple locations along the Florida Keys Reef Tract during the disease progression in March 2019. Students were able to observe sites where SCTLD had been present for over two years and sites where the disease was only just emerging for observational comparison. Student educational outcomes from field trips and activities will be discussed. Current research and educational activities can interact to enhance each other, creating a positive feedback loop. Future directions for research, educational opportunities, and their interaction to accelerate understanding of this novel disease are discussed.